Epithelial and neural cadherin expression in the mammalain reproductive tract and gametes and their participation in fertilization-related events - Vazquez, Monica Hebe (2015)
Mammalian fertilization involves a series of well-orchestrated cell-cell interaction steps between gametes, as well as among spermatozoa and somatic cells of both the male and female reproductive tracts. Cadherins are Ca(2+)-dependent glycoproteins that have been involved in cellular adhesion and signaling in somatic cells. Taking into account that Ca(2+) ions are required during fertilization, the involvement of these proteins in adhesion events during this process can be anticipated. This report presents an overview on two members of classical cadherins, Epithelial (E-) and Neural (N-) cadherin in reproductive biology. Its provides evidence of studies done by several research groups about the expression of E- and N-cadherin during spermatogenesis, oogenesis and folliculogenesis, and their involvement in gamete transport in the reproductive tracts. Moreover, it describes current knowledge of E- and N-cadherin presence in cells of the cumulus-oocyte complex and spermatozoa from several mammalian species, and shows gathered evidence on their participation in different steps of the fertilization process. A brief summary on general information of both proteins is also presented.